2003
DOI: 10.1016/s0960-9822(03)00093-9
|View full text |Cite
|
Sign up to set email alerts
|

Female Control of Male Gamete Delivery during Fertilization in Arabidopsis thaliana

Abstract: Fertilization in both animals and plants relies on the correct targeting of the male gametes to the female gametes. In flowering plants, the pollen tube carries two male gametes through the maternal reproductive tissues to the embryo sac, which contains two female gametes. The pollen tube then releases its two male gametes into a specialized receptor cell of the embryo sac, the synergid cell. The mechanisms controlling this critical step of gamete delivery are unknown. Here, data based on the new sirène (srn) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
273
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(284 citation statements)
references
References 17 publications
9
273
0
2
Order By: Relevance
“…A synergid cell represents the point of initial cell-cell contact between the male and female gametophyte. Upon contact, pollen tubes discharge their sperm cells into the synergid (in less than a minute) (33,34). In contrast to WT fertilization, Ͼ50% of mutant pollen failed to discharge sperm, despite having reached the embryo-sac.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A synergid cell represents the point of initial cell-cell contact between the male and female gametophyte. Upon contact, pollen tubes discharge their sperm cells into the synergid (in less than a minute) (33,34). In contrast to WT fertilization, Ͼ50% of mutant pollen failed to discharge sperm, despite having reached the embryo-sac.…”
Section: Resultsmentioning
confidence: 99%
“…This RT-PCR result confirms the GUS reporter analysis indicating that ACA9 is expressed in the male gametophyte, but not the female gametophyte. Finally, a publicly available oligo-based (Affy GeneChip) expression profiling analysis of pollen (http:͞͞ssbdjc2.nottingham.ac.uk͞narrays͞ experimentbrowse.pl) revealed that ACA9 was the most highly expressed of all ACAs in mature pollen, including genes for known and expected plasma membrane Ca 2ϩ pumps, such as ACA8 and ACA10 (e.g., ACA9 expression was 20-fold more than ACA8) (34). Significant ACA9 expression was observed starting at the tricellular pollen stage.…”
Section: Aca9 Is Expressed Specifically In Pollenmentioning
confidence: 99%
“…These late defects have often been interpreted as resulting from the abnormal structure of ig1 embryo sacs rather than from a requirement for ig1 in the female gametes per se. The synergids are known to attract pollen tubes (Higashiyama et al, 2001;Huck et al, 2003;Rotman et al, 2003;Marton et al, 2005), and the presence of extra synergids may promote the entry of extra pollen tubes into the embryo sac, leading to heterofertilization. Alternatively, ig1 may directly prevent these abnormal events by inhibiting embryogenesis in the egg cell until fertilization and karyogamy occur.…”
Section: Discussionmentioning
confidence: 99%
“…In an Arabidopsis mutant in which a plasma membrane Ca 21 pump of the pollen tube, ACA9, is disrupted, the pollen tube arrives at the embryo sac but cannot discharge its contents to the receptive synergid cell and shows overgrowth in the embryo sac (Schiøtt et al, 2004). ACA9 appears to be involved in intercell communication between the synergid cell and the pollen tube that triggers pollen tube discharge, along with the FERONIA and SIRENE genes that are expressed in the synergid cell (Huck et al, 2003;Rotman et al, 2003). The role of Ca 21 in gamete fusion has been suggested in a maize in vitro fertilization system; an isolated sperm cell can fuse autonomously with an isolated egg cell in the presence of a high concentration (5 mM) of calcium (Faure et al, 1994).…”
Section: Discussionmentioning
confidence: 99%